1, 7‐Bis(4‐hydroxyphenyl)‐1, 4‐heptadien‐3‐one induces lung cancer cell apoptosis via the PI3K/Akt and ERK1/2 pathways. Issue 5 (24th September 2018) - Fan, Jiangjiang; Wu, Mingsheng; Wang, Jian; Ren, Dongmei; Zhao, Jian; Yang, Guotao
Abstract: 1, 7‐Bis(4‐hydroxyphenyl)‐1, 4‐heptadien‐3‐one (EB30) is a diarylheptanoid‐like compound isolated from Viscum coloratum. This curcumin analog exhibits significant cytotoxic activity against HeLa, SGC‐7901, and MCF‐7 cells. However, little is known about the anticancer effects and mechanisms of EB30 in human lung cancer. The current study reports that EB30 significantly reduced the cell viability of A549 and NCI‐H292 human lung cancer cells. Further examination revealed that EB30 not only induced cell cycle arrest and promoted the generation of reactive oxygen species (ROS) but also induced cell apoptosis through the intrinsic and extrinsic signaling pathways. Furthermore, EB30 upregulated the expression levels of p‐ERK1/2 and p‐P90RSK, whereas downregulating the phosphorylation of Akt and P70RSK. Cell viability was further inhibited by the combination of EB30 with LY294002 (a specific PI3K inhibitor) or U0126 (a MEK inhibitor). The current study indicates that EB30 is a potential anticancer agent that induces cell apoptosis via suppression of the PI3K/Akt pathway and activation of the ERK1/2 pathway. Abstract : The results of this study indicated that EB30 could decrease cell viability, induce apoptosis, and cell cycle arrest. The induction of apoptosis was found to be mediated through the mitochondrial intrinsic pathway and extrinsic pathway. The apoptotic effects of EB30 were mediated by suppressing the PI3K/Akt pathway, whereas activating the ERK1/2 signaling.